Food Chain Inefficiency (FCI): Accounting Conversion Efficiencies Across Entire Food Supply Chains to Re-define Food Loss and Waste - Horton, Peter; Bruce, Richard; Reynolds, Christian; Milligan, Gavin (Frontiers in Sustainable Food Systems, 2019)
Achieving global food security requires a new approach that integrates not only all aspects of the growing, harvesting and processing of food (necessary to ensure sufficient affordable and sustainable production to alleviate hunger) but also the complexities associated with food consumption including deterring unhealthy overconsumption. Inefficiencies occur at various points along the agri-food supply chain but at present they are inadequately conceptualized via separate accounts of food loss, food waste, supply chain management and public health. Here we re-define food loss and waste through the concept of conversion efficiency applied to the entire system, an approach up to now only applied to the primary processes of crop productivity. Nine conversion efficiencies are defined: sunlight capture efficiency; photosynthesis use efficiency; biomass allocation efficiency; harvesting efficiency; storage and distribution efficiency; processing efficiency; retailing efficiency; consumption efficiency; and dietary efficiency. Using the production and consumption of bread in the UK as an example, we demonstrate how efficiencies may be estimated and thus where the main inefficiencies lie, so indicating where the most significant improvements could be made. We suggest that our approach, which introduces the term Food Chain Inefficiency (FCI) to re-define food loss and waste, provides a rational and effective way to devise the practical interventions and policies needed to deliver a sustainable agri-food system.